Pengaruh Metode Pembelajaran Dan Kecerdasan Interpersonal Terhadap Kompetensi Komunikasi Terapeutik Mahasiswa Program DIII Kebidanan Stikes Mitra Ria Husada Cibubur - Dina Martha; Hartati Hartati; Zulfiati Syahrial (JTP - Jurnal Teknologi Pendidikan, 2018)
This study aims to determine the method of learning and interpersonal intelligence to therapeutic communication competence of DIII students Obstetrics STIKes Mitra RIA Husada. Learning methods are placed on bedside teaching methods, coaching methods and demonstrations. The method used in this research is experiment with treatment design level 3 x 2 with sample 48 student. The summary of this research is: 1) Bedside teaching methods can improve therapeutic communication better than coaching methods and methods of demonstration; 2) Coaching learning method can improve therapeutic communication better than demonstration; 3) The existence of interaction between learning method and intelligent interpersonal to therapeutic communication competence; 4) students who have high interpersonal intelligence, more appropriate use of bedside teaching methods; 5) students who have low interpersonal intelligence, more appropriate use of coaching learning methods than the method of demonstration.